Religious musical play (International Library of African Music, 1965)
“MAZUVA EKUPEDZISA” by Abraham Maraire. (Old Umtali, Rhodesia) During the year an innovation in religious musical plays was introduced at Old Umtali, Rhodesia, using exclusively indigenous music. The group of actors and choir was drawn from 50 students of the Nyadiri Teachers’ Training College
Keywords: African Music